Modern Filling Materials for Sealing Fissures (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Fissures are special natural grooves and grooves located on the tooth enamel of the chewing surface of the teeth between the chewing tubercles. The sealing method consists of obturation fissures and other anatomical depressionsHealthy teeth with adhesive materials in order to create a barrier to external cariogenic factors